2014
DOI: 10.1038/pr.2014.74
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal monocytes express antiapoptotic pattern of Bcl-2 proteins and show diminished apoptosis upon infection with Escherichia coli

Abstract: Background:Neonates show sustained inflammation after a bacterial infection, which is associated with inflammatory diseases like bronchopulmonary dysplasia or periventricular leucomalacia. Physiologically, inflammation is terminated early after the removal of the invading pathogens by phagocytosisinduced cell death (PICD) of immune effector cells. Earlier results showed reduced PICD in neonatal monocytes. The underlying molecular mechanisms are unknown. We hypothesize that the reduced PICD in neonatal monocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Inflammation seems to be a key regulatory factor for MDSC survival [24] since apoptosis may be induced by activation of the Fas-FasL pathway. We have lately shown that cord blood monocytes also show reduced apoptosis upon infection because of diminished FasL-secretion and increased expression of anti-apoptotic Bcl-proteins [16,25]. Concordantly, our present results show higher expression of the anti-apoptotic protein Bcl-2 in G-MDSC compared to PMN, and blocking Bcl-2 led to increased apoptosis rates ( Fig.…”
Section: E Coli Infection Modulates T-cell Suppressive Activity Of Gsupporting
confidence: 88%
See 1 more Smart Citation
“…Inflammation seems to be a key regulatory factor for MDSC survival [24] since apoptosis may be induced by activation of the Fas-FasL pathway. We have lately shown that cord blood monocytes also show reduced apoptosis upon infection because of diminished FasL-secretion and increased expression of anti-apoptotic Bcl-proteins [16,25]. Concordantly, our present results show higher expression of the anti-apoptotic protein Bcl-2 in G-MDSC compared to PMN, and blocking Bcl-2 led to increased apoptosis rates ( Fig.…”
Section: E Coli Infection Modulates T-cell Suppressive Activity Of Gsupporting
confidence: 88%
“…Early steps of apoptosis include externalisation of phosphatidylserine and the loss of mitochondrial membrane potential (MMP) leading to cytochrome c release and activation of effector caspases resulting in DNA‐cleavage and apoptotic demise . Infection‐associated production of reactive oxygen species (ROS) and the expression of B‐cell lymphoma 2 (Bcl‐2) family proteins have been shown as involved in regulating infection‐induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…coli- infected purified monocytes have been described [ 19 ] [ 20 22 ]. Dampening inflammation is thought to be essential for the fetal immune system to avoid rejection by the mother and termination of pregnancy [ 23 ]. Therefore reduced secretion of TNF-α could be beneficial for the fetal environment, albeit bearing the risk of reduced capacity to fight of infection and of prolonged activation of immune effector cells by due to missing pro-apoptotic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for phagocytosis-triggered activation of the pro-apoptotic cascade involving caspases -8 and -3, was described for Staphylococcus aureus [ 28 ]. Phagocytosis also regulates the expression of small Bcl-2 like proteins [ 23 ]. For the BCL-2 like protein t-Bid a connecting function to the extrinsic and intrinsic apoptosis cascade could be shown [ 29 ], defining caspase-8 as a hinge in an auto-activating loop accelerating apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Infection can also induce pyroptosis; a rapid form of cell death triggered via the formation of inflammasomes [80]. Several reports indicate that neonatal monocytes exhibit significantly reduced apoptosis following E. coli or GBS infection compared to adults, which has been associated with the up-regulated transcription of antiapoptotic proteins [81][82][83]. No studies have specifically investigated cell death in preterm infant monocytes; however, this would be informative, as decreased apoptosis may help explain the persistent inflammation that has been described during the neonatal period in very preterm infants [84].…”
Section: Apoptosis and Inflammasome Formationmentioning
confidence: 99%